Disproportionate Burden: Estimating the Cost of FAFSA Verification for Public Colleges and Universities. (September 2021) - Guzman-Alvarez, Alberto; Page, Lindsay C.
Verification is a federally mandated process that requires selected students to further attest that the information reported on their Free Application for Federal Student Aid (FAFSA) is accurate and complete. In this brief, we estimate institutional costs of administrating the FAFSA verification mandate and consider variation in costs by institution type and sector. Using data from 2014, we estimate that compliance costs to institutions in that year totaled nearly US$500 million with the burden falling disproportionately on public institutions and community colleges, in particular. Specifically, we estimate that 22% of an average community college's financial aid office operating budget is devoted to verification procedures, compared with 15% at public 4-year institutions. Our analysis is timely, given that rates of FAFSA verification have increased in recent years.